PENINGKATAN KETERAMPILAN BERBICARA MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE TALKING STICK PADA PESERTA DIDIK DI KELAS V SDN 04 SUNGAI LIMAU PADANG PARIAMAN - Lira Apriana; Ari Suriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study was motivated by the suboptimal implementation of speaking skills activities in learning, which resulted in low speaking ability among fifth-grade students at SDN 04 Sungai Limau Padang Pariaman. The purpose of this research was to examine the application of the Cooperative Learning model with the Talking Stick type to improve the speaking skills of fifth-grade students at SDN 04 Sungai Limau Padang Pariaman. This study employed a classroom action research (CAR) design using both qualitative and quantitative approaches. The research was conducted in two cycles: Cycle I consisted of two meetings, while Cycle II consisted of one meeting. Each cycle included four stages: planning, implementation, observation, and reflection. The research subjects were the teacher and 15 fifth-grade students, consisting of 9 male and 6 female students.The results showed that the learning module in Cycle I achieved a percentage score of 85.415% with a “Good” (B) qualification, which increased in Cycle II to 95.83% with a “Very Good” (SB) qualification. Teacher activity in Cycle I reached 83.33% (“Good”), improving to 97.62% (“Very Good”) in Cycle II. Student activity in Cycle I achieved 87,805% (“Good”), increasing to 100% (“Very Good”) in Cycle II. In terms of student learning outcomes, the average knowledge assessment score in Cycle I was 80 (“Good”), which rose to 93.33 (“Very Good”) in Cycle II. For the skills assessment, the average score in Cycle I was 79.44 (“Fair”), which increased to 88.05 (“Good”) in Cycle II. Based on these results, it can be concluded that the Cooperative Learning model with the Talking Stick type can effectively improve the speaking skills of fifth-grade elementary school students.